GET TO KNOW THE TYPES OF RICE DRYING EQUIPMENT - Olimov Bobir (European Science Publishing, 2024)
Currently, great attention is paid to energy-saving devices, including energy-saving grain dryers. In addition, the issue of improving the quality of drying and accelerating the drying process is still relevant. One of the most important aspects of improving the dryer is combining the benefits of multiple dryers to create combined energy efficient dryers. This article examined energy-efficient rice dryers as well as the available literature. Combines all relevant information for drying rice and for comparison by technology. Energy for a number of drying technologies, consumer data is summarized from published literature and normalized for comparison. Performance indicators are given in the industrial or laboratory conditions in which a large part of the source data is created. Our analysis shows that combined grain dryers reduce drying time compared to other types of dryers as well as provide quality drying. Combined grain dryers usually have high energy efficiency when drying steps are included.
Keywords: Drum dryer, shaft dryer, abstract boiling dryer, pneumatic dryer, conveyor dryer, combined dryer, rice, moisture, drying period, drying method.